"Na obnovi Jugoslavije radimo za Nemačku": nemački zarobljenici, antifašisti, propagandisti. - Natalija Dimić (Токови историје, 2020)
: This paper analyzes political and ideological work among the German prisoners of war in Yugoslavia, as well as the role of German prisoners played in relations between Yugoslavia and the Socialist Unity Party of Germany (SED) between 1945 and 1950. Special attention is devoted to the impact of the Yugoslav-Soviet split on the former German prisoners of war in Yugoslavia.